Non-invasive electrical markers in patients with left ventricular hypertrophy. - Nadia Sánchez Torres; Juan A. Álvarez Gómez; Margarita Dorantes Sánchez; Jesús Castro Hevia; Geovedy Martínez García; Irma Fernández Madero (ECIMED, 2011)
Introduction The left ventricular hypertrophy is related with the genesis of ventricular arrhythmiasand sudden death. Depending of the cause, different histologycalmodifications that generate different arrhythmogenic substrates, takesplace. However, few bibliographical evidences exist about the characterizationof these, with non-invasive electrical markers.Objetive To determine the presence of non-invasive electrical markers in patients withleft ventricular hypertrophy of different causes, and to relate the magnitude,of the same one, with the presence of non-invasive electrical markers.Method In the descriptive study 107 patients, with ecocardiographic diagnosis ofleft ventricular hypertrophy were included. They were assisted at the Institutode Cardiología y Cirugía Cardiovascular, between January 2005 andDecember 2007. They were classified in groups according to the ethiologyof the left ventricular hypertrophy: Pathological left ventricular hypertrophy-that included the patients with left ventricular hypertrophy generated byhigh blood pressure, aortic stenosis and hypertrophic cardiomyopathy-,and physiologic left ventricular hypertrophy -group formed by athletesfrom the national teams of oar and swimming. They were also included, 35seemingly healthy fellows without left ventricular hypertrophy as controlgroup. We obtained a high resolution electrocardiogram at rest of twelvesimultaneous derivations to determine: the late potentials, the QTc interval,the QT special dispersion, the Tp-Te interval and the Tp-Te dispersion; also,the correlation between these markers and the magnitude of left ventricularhypertrophy was stablished.Results The non-invasive electrical markers prevailed in the group of patients withleft ventricular hypertrophy of pathological cause: the late potentials werepositive in the 37,8% and the abnormal QT space dispersion in 18,3% bothwere statistically significant, the prolonged QTc interval was present in21,9% and the mean Tp-Te dispersion was 48,7±24,9ms, in a non significantway, when comparing them with the group of physiologic cause andthe control group. In the group of pathological left ventricular hypertrophythere was a prevalence of all markers, in patients with hypertrophic cardiomyopathy:the late potentials were positive in 57,1%, the QT space dispersionwas abnormal in 28,6% and the mean Tp-Te interval133,6±37,4ms in a significant manner, when comparing with those thatpresent, aortic stenosis and high blood pressure. The prolonged QTc interval38,1% and the mean of the Tp-Te dispersion were bigger in thegroup of hypertrophic cardiomyopathy 57,1±32,2 ms, although it was notsignificant in relation with the groups of patients who suffer from aorticstenosis and high blood pressure. All markers had a weak correlation withthe magnitude of left ventricular hypertrophy (r=0,179-0,292; p <0,05).Conclusions We concluded that the studied non-invasive electrical markers were morefrequent in the group of patients with pathological left ventricular hypertrophy,and inside this, in the patients with hypertrophic cardiomyopathy andthat a weak correlation exists between the magnitude of hypertrophy andthe presence of these markers.